The diet of the anchovy Engraulis encrasicolus (Linnaeus, 1758) during the spawning season in the eastern Adriatic Sea - Mustać, Bosiljka (Array, 2020)
The objective of this study was to determine, both quantitatively and qualitatively, the variability in the diet of the anchovy, Engraulis encrasicolus,during its spawning period. Samples were obtained from commercial purse seine catches (April 2014 – September 2016) from coastal and offshore fishing areas of different trophic states and zooplankton composition over the eastern Adriatic Sea. In general, decapod larvae comprise the main source of diet during the anchovies’ spawning period in terms of frequency and abundance, followed by calanoid copepods. The main copepod prey that was identified for anchovy along the eastern Adriatic coast was calanoid Temora stylifera, followed by Oncaeid copepods and Corycaeidae. Although no significant differences in diet composition regarding the anchovy’s size was observed, the contribution of copepods decreased in larger individuals, and were gradually substituted by large crustaceans - decapods, euphausiids, mysids and amphipods. However, a significant difference in prey composition between coastal and offshore areas was observed (global R=0.164, p<0.05). Beside adult copepods, offshore water anchovy fed mainly on decapod larvae and their megalopa stage, and amphipods. In the stomach of the fish caught in the coastal waters, higher contributions of euphausiids, mysids and fish eggs were observed. Prey diversity was greater in the stomach of specimens caught offshore (H’=0.59) than in the coastal Adriatic waters (H’=0.40).